ANALISA KUALITAS LAYANAN DAN DAMPAKNYA TERHADAP KEPUASAN DEBITUR KPR SALES CENTER MEDAN PT. BANK TABUNGAN NEGARA (Persero) Tbk - Ahmad Alam Faizal Hasibuan (MANAJEMEN, 2025)
This study aims to analyze the effect of Service Quality on Debtor Satisfaction (Customer Satisfaction) in financial institutions specially in KPR Sales Center Medan, PT Bank Tabungan Negara (Persero) Tbk. The Service Quality variable is measured through dimensions such as reliability, responsiveness, and empathy, while Debtor Satisfaction is measured based on the debtor's perception of the service provided. The method used is simple linear regression to analyze the relationship between the two variables. The results of the study indicate that service quality has a positive and significant effect on debtor satisfaction, with a regression coefficient of 1.044, which means that every one unit increase in service quality will increase debtor satisfaction by 1.044 units. The t-test shows a t-value of 34.936, which is greater than table 2.034, with a significance level of 0.000. In addition, the results of the determination coefficient (R²) test show that 97.3% of the variation in changes in debtor satisfaction can be explained by service quality. This study concludes that service quality is the main factor influencing debtor satisfaction, so financial institutions need to continue to improve their service quality.